Experimental investigation and statistical analysis of 3D printed electrically conductive ABS - Aditi (My University, 2025)
This study explores the design, fabrication, and performance evaluation of ABS test specimens, focusing on optimizing their mechanical and electrical properties for practical applications. The process began with developing a CAD model, which served as the basis for systematically manufacturing the test samples. Initial mechanical testing validated the fabrication approach, confirming its reliability. Furthermore, this work presents a detailed experimental and statistical investigation into the mechanical and electrical properties of 3D-printed conductive ABS parts manufactured using the Fused Deposition Modeling (FDM) process. The study aimed to optimize process parameters to enhance both tensile and compressive strength while maintaining adequate electrical conductivity for potential multifunctional applications. In the tensile strength analysis, key parameters including printing speed (PS), layer height (LH), temperature (TEMP), and infill density (ID) were varied systematically. The results showed that lower printing speeds (40 mm/s) and higher infill densities (up to 100%) contributed significantly to improved tensile performance. The highest tensile strength recorded during experimental trials was 44.56 MPa, closely matching the model prediction of 42.56 ± 3.00 MPa, validating the accuracy of the statistical model (R² = 97.94%). For compressive strength, the optimized settings included a layer height of 0.5 mm, a temperature of 245°C, and 100% infill. The best experimental compressive strength achieved was 65.89 MPa, with a model-predicted value of 65.64 ± 3.16 MPa, again confirming strong model reliability (R² = 98.39%). To ensure the robustness of the predictive models, confirmation experiments were performed using different parameter combinations. The deviation between model predictions and actual test results remained within an acceptable range (±3MPa), demonstrating high reproducibility and precision of the optimization framework. In addition to mechanical evaluation, the electrical conductivity of the printed samples was measured using an LCR meter (Fluke PM 6306). The conductivity achieved was in the order of 10⁻³ S/mm, indicating that the material maintained a satisfactory level of electrical performance even under mechanically optimized conditions. Overall, the study demonstrates that through careful selection and optimization of process parameters, it is possible to manufacture 3D-printed ABS parts that are both structurally strong and electrically conductive. These findings provide a practical and statistically validated framework for developing multifunctional components suitable for use in smart enclosures, embedded electronics, and lightweight structural applications.
Keywords: Fused Deposition Modeling; Multi Objective Optimization; ANOVA; RSM; Conductive ABS; 3D Printing in Electronics; Statistical Analysis